Mondor’s disease of the breast; Case report. - Çalışkan, Yahya Kemal (Journal of Surgery and Medicine, 2017)
Mondor's disease is sclerosing thrombophlebitis at anteriorchest wall. It was first described by Henri Mondor in 1939. Despite the use ofantibiotics, steroids, anticoagulants, no significant benefit was found.Symptomatic measures are sufficient for treatment. Mondor's disease is aself-limiting disease. Improvement is seen between 3 weeks and 6 months. Inthese cases, investigations should be done for hidden cancers in other regionof the breast. In this study, a case with this rare disease was discussed inthe context of the literature.